2008
DOI: 10.1186/1471-2326-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intramuscular influenza vaccine in patients receiving oral anticoagulation therapy: a single blinded multi-centre randomized controlled clinical trial

Abstract: Background: Influenza vaccines are recommended for administration by the intramuscular route. However, many physicians use the subcutaneous route for patients receiving an oral anticoagulant because this route is thought to induce fewer hemorrhagic side effects. Our aim is to assess the safety of intramuscular administration of influenza vaccine in patients on oral anticoagulation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
1
16
0
4
Order By: Relevance
“…24 However, studies have shown that patients on anticoagulation therapy may receive the vaccine via the IM route without an increased risk of hematoma because the immunological response following either an IM or SQ injection is similar. 11,25 Therefore, the route of administration is not expected to be a confounder in assessing the effect of influenza vaccine on INR. Likewise, time after follow-up did not appear to affect whether a difference was observed in INR levels following immunization.…”
Section: Prospective Studies -Placebo Controlledmentioning
confidence: 99%
“…24 However, studies have shown that patients on anticoagulation therapy may receive the vaccine via the IM route without an increased risk of hematoma because the immunological response following either an IM or SQ injection is similar. 11,25 Therefore, the route of administration is not expected to be a confounder in assessing the effect of influenza vaccine on INR. Likewise, time after follow-up did not appear to affect whether a difference was observed in INR levels following immunization.…”
Section: Prospective Studies -Placebo Controlledmentioning
confidence: 99%
“…Nevertheless, previous small studies have shown that i.m. injection in an aqueous vehicle can be administered safely to patients receiving anticoagulant medications without increased risk of local bleeding (32,33,34,35,36); however, the use of larger volume of oil vehicle may change such risks. This study, based on self-report, did not record any instance of post-injection haematoma, allowing us to establish plausible upper 95% confidence limits on the risk of post-injection haematoma as 0.1% for all men having TU injections, 1% for men using anticoagulant or antiplatelet medication but who interrupt that medication temporarily for the TU injection and 5.4% for men continuing to use such medication at the time of TU injection.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulated individuals may be assumed to bleed more when receiving pre-travel vaccinations; however, an RCT in Spain involving 229 patients showed that intramuscular injection of the influenza vaccine did not result in more bleeding than the subcutaneous route. 58 Medical Devices and Automated External Defibrillators Literature on implanted cardiac devices in relation to international travel is sparse. These devices, like permanent pacemakers and implanted cardioverter-defibrillators, may add complexity when passing through airport security checkpoints.…”
Section: Medical Tourismmentioning
confidence: 99%